2001
DOI: 10.1590/s0100-879x2001000900014
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic markers following beta-adrenoceptor agonist infusion in footshock-stressed rats

Abstract: Stress hormones can alter metabolic functions in adipose tissue and liver, as well as the sensitivity of rat white adipocytes and rat atrial responses to ß-adrenergic agonists. In this study, we examined the effects of three daily footshock stress sessions on the plasma corticosterone, glucose, glycerol and triacylglycerol levels of fed, conscious male rats, and on the plasma glucose, glycerol and triacylglycerol levels of the same rats following iv infusions of ß-adrenergic agonists (isoproterenol: 0.4 nmol k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
6
0
1

Year Published

2003
2003
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 34 publications
(45 reference statements)
4
6
0
1
Order By: Relevance
“…As previously reported [10,11] footshock-stress caused a glucose intolerance and increase corticosterone serum levels, in addition in the present study we demonstrated that the ingestion for 8 weeks of normolipidic diet rich in fish oil prevented these effects.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…As previously reported [10,11] footshock-stress caused a glucose intolerance and increase corticosterone serum levels, in addition in the present study we demonstrated that the ingestion for 8 weeks of normolipidic diet rich in fish oil prevented these effects.…”
Section: Discussionsupporting
confidence: 90%
“…These results demonstrated that foot-shock stress could be a useful model for studying glucose intolerance and insulin resistance [10,11]. …”
Section: Introductionmentioning
confidence: 99%
“…It is possible that once UV emissions are bound to behavioral responses of stress, both neonatal capsaicin treatment and OVA sensitization probably have no effect on emotional behavior. Furthermore, the high serum corticosterone levels detected on samples collected from stressed rats seem compatible with previously published data [36,37] and also demonstrate the efficiency of the stress model used.…”
Section: Discussionsupporting
confidence: 90%
“…The bars indicate the means ± S.E.M. example, it has been reported that blood glucose level is significantly increased in foot shock stress model (Tajima et al, 1996;Verago et al, 2001;Márquez et al, 2002;Amano et al, 2007). On the other hand, the alteration of blood glucose level in emotional stress has not been well characterized.…”
Section: Discussionmentioning
confidence: 96%